2001
DOI: 10.1001/archinte.161.14.1733
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Clinical Trial of the Serotonin Type 3 Receptor Antagonist Alosetron in Women With Diarrhea-Predominant Irritable Bowel Syndrome

Abstract: Alosetron hydrochloride, 1 mg twice daily for 12 weeks, is effective in relieving pain and some bowel-related symptoms in diarrhea-predominant female patients with IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
201
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(206 citation statements)
references
References 40 publications
4
201
1
Order By: Relevance
“…Patient selection based on other criteria, such as bowel habit and gender, has already been shown to be of great importance for the outcome of clinical trials evaluating the efficacy of several contemporary compounds for IBS, for example alosetron and tegaserod. 23,24 Our study indicates that until clear criteria or alternative methods have been established to select individual hypersensitive patients, evaluation of perceptual thresholds to gut distension is still required. We perceive that such an approach would be very demanding if not impossible in large scale clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection based on other criteria, such as bowel habit and gender, has already been shown to be of great importance for the outcome of clinical trials evaluating the efficacy of several contemporary compounds for IBS, for example alosetron and tegaserod. 23,24 Our study indicates that until clear criteria or alternative methods have been established to select individual hypersensitive patients, evaluation of perceptual thresholds to gut distension is still required. We perceive that such an approach would be very demanding if not impossible in large scale clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Approval of this medication was based on several large randomized controlled-trials that found alosetron (1 mg po twice daily) was more effective than placebo in controlling abdominal pain and discomfort in IBS-D [40][41][42][43] . Alosetron was associated with a statistically significant decrease in the percentage of days with urgency, and it led to firmer stools and a decrease in stool frequency.…”
Section: -Ht3 Antagonistsmentioning
confidence: 99%
“…One of the serotonergic receptors belongs to the 5-HT3 receptor subtype [50] .Efficacy of blockade of 5-HT3 receptors by a 5-HT3 antagonist in the treatment of diarrhea in the diarrhea-predominant population of women with IBS [51,52] suggests that hyperstimulation of secretomotor neurons by serotonin is a significant factor in this form of IBS. Observations that IBS symptoms of cramping abdominal pain, diarrhea and fecal urgency are commonly exacerbated in the postprandial state [7,53] and evidence for elevated postprandial release of serotonin [54,55] suggests that overactive release of serotonin from the enterochromaffin cell population might underlie the diarrheal symptoms of IBS.…”
Section: Excitatory Input To Secretomotor Neuronsmentioning
confidence: 99%